Sydafrika och historien: Om gestaltningar av det förflutna under 1900-talet - Witz, Leslie; Rassool, Ciraj; Minkley, Gary (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2000)
This article deals with the construction of public history in South Africa during the 1990's. Two examples are used to problematize the claims of history being based on written sources and heritage. The authors want to take the field of heritage seriously. McGregor Museum, a flagship in the Northern Cape province, has tried to transform the old excluding radial story told there to a new All South African History. They have tried an Addition of Method. The Historians and the experts in heritage have failed to integrate the old and the new and this is part of the failure. South African Museum is another museum that is criticized not least for its Bushman-Diorama. Ratanga Junction Theme Park — the wildest place in Africa — is an example of a South-African Disneyland of the new economy. This essay is written within the project Visual Cultures in Dialogue, which is a mutual exchange programme between Umeå University and South African partners, in this case History Department in University of the Western Cape. The project is sponsored by Sida.